Impact of biological treatments of bio-waste for nutrients, energy and bio-methane recovery in a life cycle perspective. (June 2016) - Di Maria, Francesco; Micale, Caterina; Contini, Stefano; Morettini, Emanuela
Highlights: Comparative LCA of composting and several AD option of bio-waste. Electricity substitution by the biogas showed lower impact than NG substitution with bio-methane. Only composting showed avoided resource depletion. Higher uncertainty was detected for the values of GWP and POF. Abstract: Composting of the source-segregated organic fraction of municipal solid waste was compared in a life cycle perspective with conventional anaerobic digestion (AD), aimed at electricity substitution, and with AD aimed at biogas upgrading into bio-methane. Three different uses of the bio-methane were considered: injection in the natural gas grid for civil heating needs; use as fuel for high efficiency co-generation; use as fuel for vehicles. Scenarios with biogas upgrading showed quite similar impact values, generally higher than those of composting and conventional AD, for which there was a lower impact. A decisive contribution to the higher impact of the scenarios with bio-methane production was by the process for biogas upgrading. In any case the substitution of natural gas with bio-methane resulted in higher avoided impacts compared to electricity substitution by conventional AD. The uncertainty analysis confirmed the positive values for eutrophication, acidification and particulate matter. Large uncertainty was determined for global warming and photochemical ozone formation.